RENEWABLE ENERGY A NONTECHNICAL GUIDE - Wagman, David C. (PennWell Books, 2024)
Everything you need for a solid understanding of renewable energy is here in this easy-to-understand guide. David Wagman draws on his decades of experience as an energy journalist to deliver an unparalleled guide to the array of technologies that have rapidly grown to become a leading source of electric power. Using a straightforward approach, the book first draws a vivid portrait of renewable energy in its historical context and describes basic principles of energy, then introduces and explains major concepts and applications of solar, wind, hydroelectric, geothermal, biomass, and hydrogen both in North America and globally. It next offers insights into the challenges facing renewable energy, including supply chain, cybersecurity, grid reliability, recycling, and, increasingly in some markets, NIMBY opposition. Taking a forward look, it offers future considerations as the world navigates an uncertain climate and the growing imperative to decarbonize. The volume considers a range of scales from utility-sized hydroelectric plants to residential and commercial rooftop solar panels. Additionally, it includes a glossary of terms and provides a useful list of books, journals, and web sites for additional reading and reference.